The English Primary National Strategy in four schools: a policy trajectory and case study - Curtis, Robert E. (2010)
This thesis investigates the multi-faceted approach to primary school improvement, the English Primary National Strategy, in two distinct stages; the first focussed on policy texts and discourses. I tell my story, from being a headteacher, through to becoming a researcher, positioning this research within the context of policy sociology. I examine the historical development of primary education, identifying themes leading to a critical analysis of the introductory Strategy document Excellence and Enjoyment (DfES 2003) and subsequent policy initiatives.